CITA-CITA ANAK PANTI ASUHAN PUTERI AISYIYAH WILAYAH RIAU DI KOTA PEKANBARU - Zefni Defira; Achmad Hidir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This study examines the ideals of the Puteri Aisyiyah orphanage children in the Riau region in Pekanbaru City. The purpose of this study is to find out about the ideals of orphanage children and how their efforts are to achieve these goals. In determining the informants, a saturated sampling technique or a census was used, namely all 8 children from the orphanage who were studying at a Vocational High School. The theory used is rational choice theory by James Coleman. The research results obtained are all informants have ideals with their own reasons. After graduating from Vocational High School, there were informants who chose to continue their education to college and some wanted to work immediately. All informants make various efforts to achieve their goals. Some informants have skills and talents that influence them in deciding their goals, and other informants' aspirations are influenced by the majors they take in Vocational High Schools. All informants have resources as supporting factors in achieving their goals, namely parental support, inheritance, and savings. Of all the informants, some are rational and some are irrational with their efforts and resources to achieve the desired goals.